2019
DOI: 10.1080/14756366.2019.1660654
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and derivatisation of active polysaccharides

Abstract: Polysaccharide, as one of the main components of traditional Chinese medicine, has an important antioxidant effect, and its mechanism has been studied by more and more researchers. The preparation methods of Chinese traditional medicine polysaccharides and their derivatives were reviewed. In addition, the advantages and disadvantages of various preparation methods of different Chinese medicine polysaccharides and their derivatives were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…Polysaccharide extraction applying different enzymes The water-boiling method has been the historic polysaccharide extraction method used in traditional Chinese medicine, which has many disadvantages, such as the high temperatures and extended length of time required. 29 Alternatively, we used ultrasonic assisted enzymes to extract Lanzhou lily polysaccharides within a short timeframe and under low temperatures. This method does not deteriorate any of the constituents extracted using traditional Chinese medicine.…”
Section: Resultsmentioning
confidence: 99%
“…Polysaccharide extraction applying different enzymes The water-boiling method has been the historic polysaccharide extraction method used in traditional Chinese medicine, which has many disadvantages, such as the high temperatures and extended length of time required. 29 Alternatively, we used ultrasonic assisted enzymes to extract Lanzhou lily polysaccharides within a short timeframe and under low temperatures. This method does not deteriorate any of the constituents extracted using traditional Chinese medicine.…”
Section: Resultsmentioning
confidence: 99%
“…The ethanol extraction method mainly removed ethanol-insoluble substances such as polysaccharides. It was reported that the polysaccharide had reduced solubility in a higher concentration of alcohol [ 42 , 43 ]. Using this principle, the polysaccharide precipitates when the alcohol solvent is added to the boiled water extracts of QXT.…”
Section: Discussionmentioning
confidence: 99%
“…Using this principle, the polysaccharide precipitates when the alcohol solvent is added to the boiled water extracts of QXT. Polysaccharide is one of the effective components of many traditional Chinese medicines and has many functions, such as antioxidation [ 43 ]. Therefore, it is likely that the antioxidant active ingredients in QXT are not ethanol-insoluble substances, such as polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides, which are macromolecules composed of long chains of monosaccharide units, are the key bioactive components of TCMs, and they possess immunomodulatory, antitumor, anti-in ammatory, hypoglycemic, anti-aging, and antioxidant effects [34][35][36][37]. In our previous study, the polysaccharide KSWP was isolated from Kochia scoparia fruit.…”
Section: Discussionmentioning
confidence: 99%